Peran Mediasi Komitmen Organisasi pada Pengaruh Kompetensi, Semangat Kerja, dan Motivasi Terhadap Kinerja Pegawai - Fatkhul Izar; Euis Soliha (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Employee performance is important in producing the quality and quantity of institutional work results. However, employee performance still shows fluctuations so organizational targets are not achieved. Therefore, this study examines the effect of competence, work spirit, and work motivation on organizational commitment. Furthermore, the study aims to analyze the mediating role of organizational commitment on the relationship between competency factors, work spirit, and work motivation on employee performance. A total of 101 employees of Sayung I and Sayung II Health Centers in Demak, Central Java participated as research samples. The primary data collected were then analyzed using multiple linear regression. The study's results revealed that competence has a positive influence on organizational commitment, work spirit has a positive influence on organizational commitment, and work motivation has a positive contribution to organizational commitment. Further findings explain that competence, work spirit, work motivation, and organizational commitment positively influence employee performance. Furthermore, this study concludes that organizational commitment mediates the relationship between competence, work spirit, work motivation, and employee performance. The This study contributes by emphasizing human resources management literature.